Identifying the optimal ratio from protein foods for protein and nutrient quality in plant-based meals using a non-linear optimization approach - Rolands, Maryann R.; Mainardi, Fabio; Bochud, Murielle; Lê, Kim-Anne (Frontiers in Nutrition, 2025)
BackgroundPlant-based diets with reduced animal protein intake are increasingly recommended for health and sustainability reasons that have potential implications for nutrient intake, including protein quality.ObjectiveTo develop a non-linear optimization model to determine the optimal ratio needed from plant and animal protein foods to obtain a high protein and nutrient quality in primarily plant-based meals.MethodsSixty-two protein foods were grouped by their limiting amino acid: “lysine-limiting” foods were mainly “grains, nuts and seeds,” “sulfur amino acids” mainly consisted of “beans, peas and lentils” and “non-limiting” included “soy-foods” for vegan and vegetarian meals and/or “animal protein foods” for pesco/semi-vegetarian meals.” A non-linear optimization approach was used to maximize protein quality using the Protein Digestibility Corrected Amino Acid Score (PDCAAS 1) while considering essential nutrients such as energy, protein, dietary fiber, iron, calcium, and zinc in three plant-based meal models. The three models considered all contained protein foods from the first two groups, “grains, nuts and seeds” and “beans, peas, lentils, and others” and some variations of the third group being either “soy-foods only” (vegan), “soy-foods, dairy and egg” (vegetarian), or “soy-foods and/or animal-based foods” (pesco/semi-vegetarian).ResultsTo achieve optimal protein quality, calcium, iron, and zinc levels in a vegan and vegetarian meal, the optimal protein ratio based on total protein intake was at least 10% grains, nuts, and seeds; 10–60% beans, peas, and lentils; and 30–50% soy-based foods only and/or dairy and eggs. The optimal pesco/semi-vegetarian meal had at least 10% grains, nuts, and seeds, 50–60% beans, peas, and lentils, and 30–40% from soy-foods and/or animal-based foods. The vegan meal had more variety than models including animal protein foods.ConclusionThe optimal ratios of protein foods determined could be used to define easy-to-follow guidance for selecting protein foods that deliver high protein quality while also contributing to nutrient quality in primarily plant-based meals.